Mediation test for self-efficacy on the relationship between individual-related factors and knowledge sharing behaviour among Malaysian farmers - Brooke, Jenefer; Mohd Rasdi, Roziah; Abu Samah, Bahaman (Human Resource Management Academic Research Society, 2017)
This study is to investigate the predictors of knowledge sharing behaviour and mediating variable of self-efficacy among successful farmers in selected Malaysian states. In Malaysian agriculture context, knowledge sharing behaviour of successful farmers formally and informally occurs during training, farm visits and also through discussions. However, current practices among farmers in the sharing process are unstructured and lack clarity. To date, there is no certain mechanism or coordination, which can be followed and properly implemented, leaving the issue unclear and unresolved. Hence, examining how individuals’ personal factors affect shape successful farmers’ knowledge sharing behaviour is imperative in order to formulate a strategy towards encouraging knowledge sharing culture in the agriculture community. This study was quantitative in nature and involved a total of 241 farmers as the respondents. The findings indicates that self-efficacy mediates the relationship between prior experiences on knowledge sharing behaviour. In contrast, it was found that self-efficacy did not mediate the relationship between training and knowledge sharing behaviour. This study hopes to provide knowledge especially for extension agents and department of agriculture to give attention on individual-related factors which could influence self-efficacy and thereby provide practical means to improve knowledge sharing behaviour among farmers in Malaysia.